Role of organic components in regulating denitrification in the coastal water of Daya Bay, southern China. Issue 5 (24th April 2019) - Zeng, Jian; Chen, Min; Guo, Laodong; Lin, Hui; Mu, Xinyue; Fan, Linfang; Zheng, Minfang; Qiu, Yusheng
Abstract : The impact of dissolved and particulate organic mater on coastal water denitrification is evaluated. Particulate organic matter and its composition play a dominant role in regulating denitrifying activity. Abstract : Both dissolved and particulate organic materials have been proposed to be important factors in regulating heterotrophic denitrification in various aquatic environments. However, the specific pathways and mechanisms remain elusive. In this study, water column samples were collected from Daya Bay, southern China, to examine the relationships between potential denitrification and different organic components in the water column. Bulk dissolved organic carbon (DOC) was categorized into three major components including terrigenous fluorescent (tFDOC), autochthonous fluorescent (bFDOC) and non-fluorescent (nFDOC) fractions, while the bulk particulate organic carbon (POC) was divided into terrigenous (tPOC) and autochthonous (bPOC) fractions based on an isotope mixing model. Potential denitrification derived from in situ incubation experiments under anoxic conditions was evident (ranging from 6 to 107 nmol N2 per L per h) and varied markedly among stations. When normalized to nitrate concentration, the denitrification rate (NDR) followed a positive trend with either the concentration or proportion of tFDOC, and a negative trend with the proportion of nFDOC, suggesting tFDOC was potentially favorable while nFDOC was unfavorable for denitrifying degradation. In comparison, the NDR showed a significant positive correlation with the proportion of bPOC in the bulk POC ( p = 0.01), with a predictive power of >70%, indicating that the composition of POC has a substantial impact on potential denitrification. Furthermore, if both bPOC and suspended particulate matter (SPM) were considered as variables concurrently, the variability of NDR can be better predicted with a predictive power as high as 80%. Therefore, denitrifiers may preferentially utilize fresher and labile autochthonous POC instead of DOC especially in coastal waters where particles/colloids are abundant. Our results thus provide new insights for a better understanding of denitrification mechanisms in water columns and the importance of both suspended particles and POC components in regulating denitrification, especially in turbid and productive coastal environments.